The adult abdominal neuromuscular junction of Drosophila: a model for synaptic plasticity. - Hebbar, S.; Hall, R.E.; Demski, S.A.; Subramanian, A.; Fernandes, J.J. (Journal of Neurobiology, 2006)
During its life cycle, Drosophila makes two sets of neuromuscular junctions (NMJs), embryonic/larval and adult, which serve distinct stage-specific functions. During metamorphosis, the larval NMJs are restructured to give rise to their adult counterparts, a process that is integrated into the overall remodeling of the nervous system. The NMJs of the prothoracic muscles and the mesothoracic dorsal longitudinal (flight) muscles have been previously described. Given the diversity and complexity of adult muscle groups, we set out to examine the less complex abdominal muscles. The large bouton sizes of these NMJs are particularly advantageous for easy visualization. Specifically, we have characterized morphological attributes of the ventral abdominal NMJ and show that an embryonic motor neuron identity gene, dHb9, is expressed at these adult junctions. We quantified bouton numbers and size and examined the localization of synaptic markers. We have also examined the formation of boutons during metamorphosis and examined the localization of presynaptic markers at these stages. To test the usefulness of the ventral abdominal NMJs as a model system, we characterized the effects of altering electrical activity and the levels of the cell adhesion molecule, FasciclinII (FasII). We show that both manipulations affect NMJ formation and that the effects are specific as they can be rescued genetically. Our results indicate that both activity and FasII affect development at the adult abdominal NMJ in ways that are distinct from their larval and adult thoracic counterparts